Clinical genetics in transition—a comparison of genetic services in Estonia, Finland, and the Netherlands - Vrijenhoek, T. (J Community Genet, 2021)
Genetics has traditionally enabled the reliable diagnosis of patients with rare genetic disorders, thus empowering the key role of today’s clinical geneticists in providing healthcare. With the many novel technologies that have expanded the genetic toolkit, genetics is increasingly evolving beyond rare disease diagnostics. When placed in a transition context—like we do here—clinical genetics is likely to become a fully integral part of future healthcare and clinical genetic expertise will be required increasingly outside traditional clinical genetic settings. We explore transition effects on the thinking (culture), organizing (structure), and performing (practice) in clinical genetics, taking genetic healthcare in Estonia, Finland, and the Netherlands as examples. Despite clearly distinct healthcare histories, all three countries have initially implemented genetic healthcare in a rather similar fashion: as a diagnostic tool for predominantly rare congenital diseases, with clinical geneticists as the main providers. Dynamics at different levels, such as emerging technologies, biobanks and data infrastructure, and legislative frameworks, may require development of a new system attuned with the demands and (historic) context of specific countries. Here, we provide an overview of genetic service provisions in Estonia, Finland, and the Netherlands to consider the impact of historic and recent events on prospective developments in genetic healthcare.